First population study of the general public awareness and perception of epilepsy in Bosnia and Herzegovina - Bagić, Anto (Array, 2009)
Public knowledge of, perception of, and attitudes toward epilepsy in Bosnia and Herzegovina (BH) were studied for the first time. One thousand randomly selected adults were asked 12 questions about epilepsy. Ninety-one percent (91%) of respondents had heard about epilepsy, 41% knew someone with epilepsy, 32.5% had witnessed a seizure, and 33.1% did not know any of the symptoms of epilepsy. On average, interviewees were ready to accept a person with epilepsy. Approximately 15% would object if their child played with a child with epilepsy, and 39% believed that a child with epilepsy could not succeed as well as a child without epilepsy. Although 55.9% would approach a person experiencing a seizure and help, 25.9% would call ‘ ‘ 911.” Positive attitudes correlated with nowing someone with epilepsy and/or witnessing a seizure. General awareness of and attitudes toward epilepsy in BH approach those of developed countries. These results are somewhat more favorable than expected and an encouraging foundation for a necessary public health awareness campaign.